Pengaruh Media Sosial, E-Service Quality dan Harga Terhadap Keputusan Pembelian yang di Mediasi Oleh Gaya Hidup - muslim, Abdul wahid (Universitas Sam Ratulangi, 2018)
The purpose of this study is to describe and analyze the influence of social media e-service quality and price on purchase decisions, mediated by lifestyle on consumer of music streaming application Spotify in Manado. Result of the research shows that social media have a significant effect on lifestyle. E-service quality has a significant effect on lifestyle. Prices also have a significant effect on lifestyle. Meanwhile, social media has no significant effect on purchasing decisions. E-service quality also has no significant effect on purchasing decision.In this study also found that price have a significant effect on purchasing decisions, and lifestyle has a significant effect on the purchase decision on consumer of music streaming application Spotify in Manado.Keywords: Media Social, E-Service Quality, Price, Lifestyle, Purchasing Decision